2011
DOI: 10.1016/j.ijsu.2011.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical activation of coagulation and fibrinolysis in laparoscopic cholecystectomy: Do risk factors exist?

Abstract: Despite no DVT, significant increase in PT-INR, d-dimer, FDP and fibrinogen appeared after LC. This may be attributed to surgical trauma and pneumoperitoneum effects on the portal vein flow. Elderly subjects and males seem particularly vulnerable, demonstrating more sizeable changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…38 More sizeable changes in coagulation activation were observed in the elderly patients. 33 Perioperative changes in blood coagulation during laparoscopic cholecystectomy were smaller than during open cholecystectomy, 34,35 and changes were no greater than observed following low-risk surgery. 36 Strengths of these data are the huge number of patients with data obtained over 11 years from all regions of United State, all ethnicities, both genders, and all age groups.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…38 More sizeable changes in coagulation activation were observed in the elderly patients. 33 Perioperative changes in blood coagulation during laparoscopic cholecystectomy were smaller than during open cholecystectomy, 34,35 and changes were no greater than observed following low-risk surgery. 36 Strengths of these data are the huge number of patients with data obtained over 11 years from all regions of United State, all ethnicities, both genders, and all age groups.…”
Section: Discussionmentioning
confidence: 86%
“…27 Several investigations showed markers of postoperative hypercoagulability. [30][31][32][33][34][35][36][37] One investigation showed no hemostatic changes in blood draining the lower limbs. 38 More sizeable changes in coagulation activation were observed in the elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ntourakis et al showed in a observational study of 119 Blow risk^VTE patients undergoing elective laparoscopic cholecystectomy that elderly patients (>70 years) not only had a higher concentration of D-dimer preoperatively, but also expressed significantly higher postoperative Ddimer levels on the first day after surgery compared to younger patients [30]. Hence, a raised coagulation response in elderly patients and an observed increased risk for developing postoperative PE after cholecystectomy warrants a more liberate use of TP in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of the length of PT and APTT before and after the surgery did not demonstrate any statistically significant differences [27][28][29].…”
Section: Von Willebrand Factormentioning
confidence: 74%